Integrated pest management - Paparella, Antonio; Petsakos, Athanasios; Davis, Kristin E.; Song, Chun (International Food Policy Research Institute, 2025)
The use of pesticides in agriculture has had mixed consequences. While pesticides have significantly increased agricultural productivity and food security by reducing yield losses to harmful organisms [1], their excessive use has led to severe environmental consequences. Inherently, pesticides are designed to protect plants from pests. However, their effects extend far beyond the targeted organisms. Pesticides occasionally contaminate soil [2], [3], [4], water [5], [6], and air [7], leading to widespread environmental pollution, reducing biodiversity and causing potential health risk to humans [8]. This happens through volatilization [9], spray drift [10], runoff from fields [11], and improper product management [12] such as improper disposal of empty containers or incorrect dosage [12]. The chemicals used in pesticides can persist in the environment, causing long-term harm to ecosystems [13]. They do not stay confined to the areas where they are applied; they can spread through air and water, affecting distant ecosystems and non-target species.